063 Improving service provision for patients with suspected idiopathic intracranial hypertension in a joint neuro-ophthalmology clinic. Issue 6 (27th May 2022) - Dokal, Kitt; O'hanlon, Ciaran; Castelhano, Rute; Yiin, Gabriel; Hinze, Stephan; Pandit, Jyotin; Morrish, Paul; Paul, Nicola
Abstract : Introduction: Care of patients with suspected Idiopathic Intracranial Hypertension (IIH) involves neurolo- gists and ophthalmologists, however this can be difficult to co-ordinate. Consensus guidelines suggest all patients with suspected IIH should have weight, visual fields, neuroimaging and a CSF opening pressure. The aim of our study was to determine adherence to consensus guidelines. Methods: We assessed medical notes of consecutive patients attending the new joint neuro-ophthalmol- ogy clinic in the Great Western Hospital, Swindon between 1st September–31st December 2020. Due to the Covid-19 pandemic a neurologist was not always present. Results: Of 38 patients attending the clinic with suspected IIH, 35(92%) were female. 29(76%) had weight recorded; 14(37%) patients had BMI recorded, 12(32%) had BP recorded; 36(95%)had visual fields recorded, 12(32%) and 17(45%) respectively had whether neuroimaging or lumbar puncture were required. 23(61%) had weight management discussed, 22(58%) had a medication review discussed. Conclusion: Documentation of weight, BMI, BP, investigation results and management discussions could be improved in the joint neuro-ophthalmology clinic. We aim to address this by introducing an "IIH clinic checklist" for use by clinicians and patients to help improve adherence to consensus guidelines. kitt.dokal@kcl.ac.uk